Explore The Role of Food in English Language Learning - Donny Adiatmana Ginting; Yunita Sari Adelina; Dedek Hardian Syahputra (The Seall Journal, 2023)
This study explores the role of food in English language learning. Using a qualitative approach, data were collected through interviews with language teachers and learners, classroom observations, and analysis of teaching materials. The findings suggest that food can be an effective tool for engaging learners, enhancing motivation, and facilitating language acquisition. Food-related activities such as cooking, tasting, and discussing recipes can provide authentic and meaningful contexts for language learning. Food can also serve as a bridge between different cultures and facilitate intercultural communication. However, the use of food in language classrooms should be carefully designed and implemented to avoid potential issues related to cultural appropriateness and sensitivities. The study highlights the importance of considering the cultural and pedagogical implications of using food as a language learning resource. Keywords : food, English language learning, motivation, language acquisition, culture, intercultural communication